User involvement in the making: Positions and types of knowledge enacted in the interaction between service users and researchers in user panel meetings - Per Koren Solvang; Unni Sveen; Helene Lundgaard Søberg (Wiley, 2021)
Abstract Background Numerous studies of user involvement in research have been conducted. However, there is a lack of studies applying observational methods and addressing the concrete practice of involvement. Objective To determine what knowledge types and competences users apply when involved in the research process through user panel meetings. Design User panel meetings in a qualitative project in rehabilitation were sound‐recorded and transcribed verbatim. Data analysis applied an abductive approach framed by positioning theory. Setting and participants Six rehabilitation service users and a similar number of researchers met 20 times during a six‐year project period. They discussed various issues in the research process such as interview guides, analysis and dissemination of results. Findings The service users combined their respective knowledge and competence into six positions enacted in the panel interactions. They engaged as co‐researchers, based their contributions on their respective personal histories, represented an NGO and peers, applied their respective professional and educational backgrounds and, finally, engaged as concerned citizens. Discussion and conclusion The findings add to the discussion of professionalization of user involvement by introducing a wider array of positions enacted than do the findings of previous studies. Researchers recruiting user panel members, as well as NGOs appointing candidates for user panels, are advised to consider a wide competence profile for possible candidates. A panel is also considered as a resource in confirming and elaborating on a study's findings. Patient and public contribution A service user panel contributed to the study.